2021
DOI: 10.1093/cvr/cvaa344
|View full text |Cite
|
Sign up to set email alerts
|

Stroke risk prediction in patients with atrial fibrillation with and without rheumatic heart disease

Abstract: Aims Patients with atrial fibrillation (AF) and rheumatic heart disease (RHD), especially mitral stenosis, are assumed to be at high risk of stroke, irrespective of other factors. We aimed to re-evaluate stroke risk factors in a contemporary cohort of AF patients. Methods and results We analysed data of 15 400 AF patients presenting to an emergency department and who were enrolled in the global RE-LY AF registry, representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The majority of the studies validated a risk score in a general predominantly Caucasian AF population, with the exception of studies validating prior or post-surgery ( n = 6), 60–65 in cohorts with a specific secondary disease ( n = 11), 42 , 44 , 66–74 or in cohorts with ethnicity other than predominantly Caucasian ( n = 20). 33 , 34 , 45 , 47 , 53 , 55 , 65 , 71 , 75–87 Discrimination was presented in all studies ( n = 107) and indicated poor (<0.60) to reasonable (0.60–0.80) and in exceptional cases good (>0.80) discrimination; these values are visualized in the forest plots given in Supplementary material online, section ‘Random-effects meta-analysis’ . For the risk scores developed after the publication of the CHA 2 DS 2 -VASc (2010), no discrimination lower than 0.60 was reported in the validation studies.…”
Section: Resultsmentioning
confidence: 97%
“…The majority of the studies validated a risk score in a general predominantly Caucasian AF population, with the exception of studies validating prior or post-surgery ( n = 6), 60–65 in cohorts with a specific secondary disease ( n = 11), 42 , 44 , 66–74 or in cohorts with ethnicity other than predominantly Caucasian ( n = 20). 33 , 34 , 45 , 47 , 53 , 55 , 65 , 71 , 75–87 Discrimination was presented in all studies ( n = 107) and indicated poor (<0.60) to reasonable (0.60–0.80) and in exceptional cases good (>0.80) discrimination; these values are visualized in the forest plots given in Supplementary material online, section ‘Random-effects meta-analysis’ . For the risk scores developed after the publication of the CHA 2 DS 2 -VASc (2010), no discrimination lower than 0.60 was reported in the validation studies.…”
Section: Resultsmentioning
confidence: 97%
“…Progressive increases in left atrial dimensions, in conjunction with atrial inflammation, can lead to the development of AF in patients with rheumatic MS [11][12][13]. Meta-analyses of over 75 000 patients with RHD suggests an AF prevalence rate of upward of 33% with higher rates seen in those with mixed MS and mitral-regurgitation (MR) phenotype [14].…”
Section: Atrial Fibrillation and Stroke Risk In Rheumatic Heart Diseasementioning
confidence: 99%
“…Many reviews often quote the risk of stroke in patients with AF and RHD to be approximately 18-fold higher than patients without AF-a number that was generated from studies in the 1970s when anticoagulation was used infrequently or incorrectly [13,16]. In a series of recent articles, Karthikeyan et al [12] and Benz et al [13] detail that…”
Section: Atrial Fibrillation and Stroke Risk In Rheumatic Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…3 In patients with RHD, AF is associated with increased prevalence of heart failure, stroke, peripheral embolism and death. [4][5][6][7] Especially, about 80% of the strokes in patients with RHD occur in patients with mitral stenosis and AF. 8 Guidelines recommended that surgical ablation for AF could be performed without additional risk of operative mortality or major morbidity, and was recommended at the time of concomitant MV operations to restore sinus rhythm (class I, level A).…”
Section: Introductionmentioning
confidence: 99%